Private tutoring participation among form three students in Malaysian rural and urban schools / Magaswari Ubbudari - Magaswari, Ubbudari (2017)
Commencing 2014, the Malaysian Government has introduced a new school based assessment system (PT3) for Form Three students. The purpose of this study is to analyse the determinants of private tutoring (PT) among Form Three students and to determine whether changes in the assessment system affects the demand and dimension of private tutoring. Additionally, this study uses advanced econometric analysis to identify whether private tutoring helps to improve the performance of Form Three students. The study also examines reasons for students’ participation in private tutoring for non-examination subjects (History and Geography).This research applied both quantitative and qualitative methodology. Stratified sampling was used to select students of different academic ability from ten schools in five zones in Malaysia. One school is chosen respectively from urban and rural area of each zone. Questionnaires were self-distributed to six hundred and sixty nine students. Interview was also conducted with one student from each school in the five zones. Descriptive and inferential statistics were used to analyze the quantitative data. Thematic analysis was used to analyse the qualitative data. Findings of the study suggested that ethnicity, quality of school and the types of tuition provider were important determinants for students’ participation in private tutoring for examination and non-examination subjects. The results showed that location was a significant factor that determined students’ participation in private tutoring for non-examination subjects but it was not a significant factor for examination subjects. Findings also revealed that participation in private tutoring was an important factor that determines the greater number of A’s that students obtain in PT3 assessment. Ordered logistic regression showed that an increase in Malay ethnicity increased the log odds by 2.56 for obtaining a higher number of A’s compared to Indian students, holding else constant. The qualitative result also suggested that students’ participation in private tutoring for History was to enhance their understanding and as preparation for Form Five (SPM) examinations since History is a compulsory subject to pass to obtain certificate in SPM. The findings provide insights to policy makers in both developing and developed countries whether the demand for private tutoring is affected when the assessment method changes.